Impact of the total solar eclipse of 29 March 2006 on the surface energy fluxes at Ibadan,Nigeria (2012)
This paper document the impact of the total solar eclipse (97.4%) of 29 March 2006 on the surface energy fluxes at Ibadan, Nigeria (longitude4.561E, latitude7.551N), a tropical location. The surface energy (determined by the BREB method) was found to be grossly affected by the eclipse. The latent heat and net radiation (Rn) lagged the sensible heat by 11 min in totality. The sensible heat lagged the latent heat and Rn by 6 min before it start to increase after the totality phase of the eclipse while global radiation (Rg) lagged Rn by 7 min. The sensible heat reversed sign reaching a value of _1.02 Wm_2 during the total phase of the eclipse while the latent heat dropped by 89.7%. All the radiation fluxes (global radiation, Rg, net radiation Rn, temperature and soil heat flux) measured during the eclipse event were significantly affected by the sudden ‘cutoff’of the solar irradiation.There was a 95% decrease in Rg, while Rn dropped from 354.3Wm_2 to _11.7 Wm_2.